Assessement of Teff [Eragrostis tef (Zucc.) Trotter] Seed Production in Local Seed Business at Halaba Special Woreda and Meskan Woreda, South Ethiopia - SAMSON SEIFE; R P S TOMER; LEMMA DESSALEGNE (Seed Research, 2026)
The Meskan and Halaba Special Woredas are among Teff producing areas of South Nations Nationalities and Peoples Regional State. Despite the fact that Woredas posses a potential for Teff production, the productivity is low due to input and quality seed related problems. Tseday (Cr-37) and Quncho (Cr-387) are the major Teff varieties grown in Halaba Special Woreda and Meskan Woreda respectively. From the survey conducted it was observed that those farmers participating in the two cooperatives were better seed secured than non-participant ones. Participant farmers used separate plot for seed production and performed extra special activity for seed production including isolation and rouging out of off types or undesirable plants. The certification practice in the region is erratic because there are only two quality control centers in the region that they could not cover all the seed production area. All the participants have produced seed contractually in the past. In this study it was vividly observed that farmers participating in the two local seed Business cooperatives in Halaba special Woreda and Meskan Woreda had the edge towards having better performance in production of Teff.